The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.fjc.0000175432.56789.e6
|View full text |Cite
|
Sign up to set email alerts
|

Lowering of Elevated Ambulatory Blood Pressure by HMG-CoA Reductase Inhibitors

Abstract: Controversial results were reported as to a possible blood pressure-lowering effect of statins. This may relate to methodological limitations (blood pressure measuring techniques) or to putative different effects of statins in different biologic conditions (cholesterol or blood pressure levels, age, etc). Patients with cholesterol>200 mg/dL and no previous statin treatment underwent 24-hour ambulatory blood pressure (ABP) monitoring and were classified as normotensives or hypertensives according to their ABP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…56 In contrast, no effect was observed in normotensive subjects. 56 Hypertensive and dyslipidaemic subjects (n ¼ 32) were treated with atorvastatin (20 mg/day) in one study.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…56 In contrast, no effect was observed in normotensive subjects. 56 Hypertensive and dyslipidaemic subjects (n ¼ 32) were treated with atorvastatin (20 mg/day) in one study.…”
mentioning
confidence: 61%
“…These findings were independent of lipid-lowering associated with statin treatment. 55 In another study, 56 hypertensive and normotensive subjects with hypercholesterolaemia were randomised to receive a statin (n ¼ 51, simvastatin 10-20 mg/day, pravastatin 10-20 mg/day or atorvastatin 5-10 mg/day) or placebo (n ¼ 23) for 2 months. Statin-treated hypertensive subjects showed lower systolic and diastolic ambulatory BP (À5.775.8 and À3.573.9 mm Hg, respectively, both Po0.001).…”
Section: Do Lipid Abnormalities Predict the Risk For Hypertension?mentioning
confidence: 99%
See 1 more Smart Citation
“…Terzoli et al [32] performed a clinical study to address the conflicting results regarding blood pressurelowering effect of statins. Patients with cholesterol >200 mg/dL and no previous statin treatment underwent 24-h ABP monitoring and were classified as normotensives or hypertensives according to their ABP.…”
Section: In Patients Without Hypertensionmentioning
confidence: 99%
“…Several clinical trials have demonstrated that statins exert beneficial effects in patients at high cardiovascular risk. 10 Moreover, several studies have shown that statins decrease blood pressure in variable degrees both in humans [11][12][13][14] and in experimental models, 15,16 although a lack of effect of statins on blood pressure levels has also been described. [17][18][19] Most of the benefits of statin therapy are attributable to the lowering of serum cholesterol levels.…”
mentioning
confidence: 99%